Knowledge and Practices Regarding Animal Bite Management and Rabies Prophylaxis Among Doctors in Delhi, India. (January 2013) - Garg, Ankur; Kumar, Rajesh; Ingle, Gopal Krishan
It was envisaged to study the knowledge and practices of doctors regarding management of animal bites and rabies. By dividing Delhi into 5 geographic zones, a representative sample of doctors was selected from government hospitals, dispensaries, and private settings. Many gaps were seen in the knowledge and practices of doctors regarding animal bite management. Less than half were aware of the intradermal rabies prophylaxis schedule (39.1%), site (42.2%), and dose (48.4%). The majority (81.4%) knew of the postexposure schedule in unimmunized patients. However, only 40.4% knew of the postexposure schedule in previously immunized patients, and 47.8% knew of the preexposure prophylaxis schedule. Government doctors had significantly better knowledge than private doctors with respect to the postexposure intramuscular schedule in unimmunized individuals, intramuscular site, dose, and classification of animal bites. There is a need for doctors in all health care settings to update their knowledge on different aspects related to animal bite management.